The Relationship Between Parents' Support Regarding Covid-19 Vaccination in Children with Children's Readiness in Following Covid-19 Vaccinations - Homsiatur Rohmatin; Leni Puji Wibiati; Mega Silvian Natalia (KHD Production, 2023)
The Indonesian Pediatrician Association notes that the number of COVID-19 cases in children in Indonesia is now the highest in Asia. This study analyzes the relationship between parental support regarding Covid-19 vaccination in children and children's readiness to participate in Covid 19 vaccination. This quantitative research design uses a correlational design using a cross-sectional study approach with 35 respondents using a total sampling technique. Data collection includes coding, editing, and tabulating, then analyzed manually and by computer with the Chi-Square Test. Based on data from 35 respondents, most of the parental support that supported the number of 26 respondents (74.3%) included the readiness of children who were ready by the number of 22 respondents (62.9%) and who were not ready by the number of 4 respondents (11.4%). obtained p-value: 0.001 and a=0.05, meaning r<a, so there is a relationship between parental support regarding Covid 19 vaccination in children with children's readiness to participate in Covid-19 vaccination.